Rekrutmen Tanpa Henti : Studi Fenomenologi Pengunduran Diri Karyawan Perusahaan Pembiayaan di Samarinda - Mohammad Romadloni; Saiful Saiful; Bejo Santoso; Yurdi Maulidani; Reza L. Hakim (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The phenomenon of employee resignation represents a serious challenge for financing companies, particularly in Samarinda, as evidenced by the recurring recruitment processes for credit marketing positions, which in turn increase operational costs and undermine team stability. This study aims to gain an in-depth understanding of the subjective experiences of employees who have resigned as well as those who remain employed but strongly intend to leave the company. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with seven informants, consisting of five former employees and two active employees. The findings reveal four key factors driving resignation decisions: intense performance pressures and heavy workloads, limited opportunities for career advancement, misalignment with organizational culture, and an imbalance between work and personal life. On the other hand, economic necessity and loyalty to team members serve as retention factors that encourage some employees to remain despite dissatisfaction. These results affirm that resignation decisions are multidimensional, shaped by a complex interplay of internal and external factors that influence employees’ working lives. The study recommends that financing companies foster a healthier organizational culture, provide clear and transparent career development opportunities, and implement policies that support work–life balance in order to reduce turnover, strengthen employee retention, and enhance long-term organizational competitiveness.